Are depression and poor sexual health neglected comorbidities? Evidence from a population sample. Issue 3 (23rd March 2016) - Field, Nigel; Prah, Philip; Mercer, Catherine H; Rait, Greta; King, Michael; Cassell, Jackie A; Tanton, Clare; Heath, Laura; Mitchell, Kirstin R; Clifton, Soazig; Datta, Jessica; Wellings, Kaye; et al.
Abstract : Objective: To examine associations between sexual behaviour, sexual function and sexual health service use of individuals with depression in the British general population, to inform primary care and specialist services. Setting: British general population. Participants: 15 162 men and women aged 16–74 years were interviewed for the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), undertaken in 2010–2012. Using age-adjusted ORs (aAOR), relative to a comparator group reporting no treatment or symptoms, we compared the sexual health of those reporting treatment for depression in the past year. Outcome measures: Sexual risk behaviour, sexual function, sexual satisfaction and sexual health service use. Results: 1331 participants reported treatment for depression (5.2% men; 11.8% women). Relative to the comparator group, treatment for depression was associated with reporting 2 or more sexual partners without condoms (men aAOR 2.07 (95% CI 1.38 to 3.10); women 2.22 (1.68 to 2.92)), and concurrent partnerships (men 1.80 (1.18 to 2.76); women 2.06 (1.48 to 2.88)), in the past year. Those reporting depression treatment were more likely to be dissatisfied with their sex lives (men 2.32 (1.74 to 3.11); women 2.30 (1.89 to 2.79)), and to score in the lowest quintile on the Natsal-sexual function measure. They were also more likely to report a recent chlamydia test (men 1.92 (1.15 to 3.20)); women (1.27 (1.01 to 1.60)), and to have sought help regarding their sex life from a healthcare professional (men 2.92 (1.98 to 4.30); women (2.36 (1.83 to 3.04)), most commonly from a family doctor. Women only were more likely to report attending a sexual health clinic (1.91 (1.42 to 2.58)) and use of emergency contraception (1.98 (1.23 to 3.19)). Associations were broadly similar for individuals with depressive symptoms but not reporting treatment. Conclusions: Depression, measured by reported treatment, was strongly associated with sexual risk behaviours, reduced sexual function and increased use of sexual health services, with many people reporting help doing so from a family doctor. The sexual health of depressed people needs consideration in primary care, and mental health assessment might benefit people attending sexual health services.